(untitled) (International Journal of Engineering and Computer Science, 2017)
Database system has evolved from a specialized computer application to a central component of a modern computing environment, and, as a result, it has become an essential part of computer science. A major responsibility of the database administrator is to prepare for the possibility of hardware, software, network, process, or system failure. If such a failure affects the operation of a database system, we must recover the database and return to normal operation as quickly as possible. Recovery should protect the database and associated users from unnecessary problems and avoid or reduce the possibility of having to duplicate work manually. Recovery processes vary depending on the type of failure that occurred, the structures affected, and the type of recovery that you perform. Recovery refers to the various strategies and procedures involved in protecting the database against data loss and reconstructing the database after any kind of failure. This paper presents a conceptual level description of various issues and techniques related to recovery.